Determinants of economic effeicency among smallholders cowpea farmers in South Africa : a case study of Capricorn and Waterberg Districts in Limpopo Province - Chauke, Shiluva Valentine (My University, 2018)
Legumes are crops that are rich in protein and if households are made aware of their importance, they can be acquired at lower costs and dependency on animal proteins can also be reduced. The cowpea smallholder producers in Africa are faced with numerous challenges such as persistent pests such as aphids that reduce yields, lack of improved varieties and the inability to produce in quantities large enough to sell to local or broader markets in South Africa. The aim of this study was to examine economic efficiency of cowpea production among smallholder cowpea farmers in Capricorn and Waterberg districts of Limpopo province. The descriptive statistics indicated that interviewed farmers years of schooling ranged from 0 to 13 years, with an average of five years of attending school. Farmers’ age ranged between 33 and 78, with an average age of 61 years. The average income received on monthly basis from the overall agricultural produce was R1735.83 per farmer. The Data Envelopment Analysis (DEA) results showed that the Technical Efficiency (TE) scores of cowpea farmers had a mean of 0,9588 with a minimum of 0,7500 and maximum of 1,000. This means that 95% of the farmers were technically efficient. The allocative Efficiency score ranges from a minimum of 0,4070 and a maximum of 1,000 with a mean of 0,6519. The Allocative Efficiency (AE) scores imply that farmers were not utilizing inputs. The Economic Efficiency scores ranges from a minimum of 0,3820 to 1,000 with a mean score of 0,6218. This implies that cowpea smallholder farmers were economically inefficient on average and that the cost of cowpea production for each farm could be decreased on average by approximately 38% to obtain the same level of output. The Tobit regression model found that the explanatory variables which were significant are age, educational level, primary income source, farm size, method of intercropping, purpose of growing cowpea and source of field labour. The study recommends that there is a need to provide primary education to the farmers for them to be able to measure and calculate the inputs they use and output they attain in order to improve their efficiency levels. Key words: Economic Efficiency, Smallholder Farmers and Data Envelopment Analysis (DEA).
Thesis (M.Sc. (Agricultural Economics)) --University of Limpopo, 2018
Keywords: Economic efficiency; smallholder farmers; Cowpea